The effect of Entamoeba histolytica lectin antigen and microRNA-643 on the development of microsatellite instability (MSI) in colorectal adenocarcinoma - Leila Haghighi; Abdolhossein Dalimi; Majid Pirestani; Fatemeh Ghaffarifar (BMC Cancer)
Abstract Entamoeba histolytica remains a significant cause of global mortality. The involvement of protozoa in microsatellite instability (MSI) and the potential of miRNA-643 as biomarkers for amoebic and colorectal diseases have not been extensively researched. The relationship between the antigenic structure of Entamoeba histolytica Lectin (Eh-lectin) and the altered expression of miRNA-643 and the X-Linked Inhibitor of Apoptosis (XIAP) is still unclear. This study aimed to identify Eh-lectin, miRNA-643, XIAP, and MSI in 150 colorectal cancer biopsy samples using a comprehensive approach that included immunohistochemistry (IHC), Multiplex PCR, RT-qPCR, and Real-Time PCR. To enhance the accuracy of MSI diagnosis, PCR-Multiplex was performed alongside IHC. Among the 150 colorectal cancer biopsy samples analyzed, 39 (comprising 28 MSI-H and 11 MSI-L) showed MSI, while the remaining 111 were MSI-negative. Notably, 11 samples demonstrated a co-occurrence of MSI and Eh-lectin, with increased expression of miRNA-643 relative to XIAP. The presence of MSI in conjunction with Eh-lectin positivity and elevated miRNA-643 expression, along with reduced levels of the XIAP inhibitor gene in colorectal adenocarcinoma biopsy samples, strongly indicates that this protozoan parasite may play a role in the development of MSI by affecting apoptosis.